Mal Administrasi dalam Kajian Pelayanan Publik dan Hukum Administrasi Negara: Sebuah Tinjauan Teoritis - Dony Azfirmawarman; Aldri Frinaldi (Universitas Negeri Padang, 2023)
Maladministration is a term that we often hear in the implementation of state administration, but number of people do not concern on this term, even a term that is closely related to with daily life, especially closely related to the public service element in the implementation of state administration. However, society in general has If you know about administrative malfeasance, you are still unable to distinguish what administrative malfeasance is, and how it differs from acts of corruption, and it is not uncommon for law enforcement officials to sometimes not be able to distinguish with certainty several deviant acts that often occur in the administration of government administration. Misadministration acts within the meaning of Article 1(3) of Law No. 37 year 2008 concerning the Ombudsman are illegal acts or actions, taking advantage of authority, using authority for purposes other than the intended purpose prescribed by jurisdiction, including abandon or carelessness of legal obligations in the performance of public services made by administrator. Countries and governments that cause material and/or immaterial damage to societies and individuals